2018
DOI: 10.1038/s41430-018-0169-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of problematic eating behaviours with food quality and body mass index at 7 years of age

Abstract: Background/objectives There is scarce evidence of how certain eating behaviours compromise the compliance with dietary guidelines and weight status in school-aged children. This study aims to evaluate the association of children's problematic eating behaviours with food quality and body mass index at 7 years of age. Subjects/methods Participants were children aged 7 years old from a population-based cohort study from Porto, PortugalGeneration XXI. Children's quantity and speed of ingestion, food refusal at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…A prospective approach is the best way to clarify these relationships The prevalence of problematic behaviours perceived by the parents (defined as any behaviours reported, independently of the level of concern) ranged from 12% to 51% at 4 years and between 19% and 52% at 7 years of age. Previous studies have found similar prevalence rates, ranging between 3 to 66% (4)(5)(6) . The present study indicated also that the parental perception of problematic behaviours increased as the child gets older.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…A prospective approach is the best way to clarify these relationships The prevalence of problematic behaviours perceived by the parents (defined as any behaviours reported, independently of the level of concern) ranged from 12% to 51% at 4 years and between 19% and 52% at 7 years of age. Previous studies have found similar prevalence rates, ranging between 3 to 66% (4)(5)(6) . The present study indicated also that the parental perception of problematic behaviours increased as the child gets older.…”
Section: Discussionmentioning
confidence: 57%
“…These questions were derived from some subscales of the CEBQ, namely FF, SE and FR. The point-biserial correlations between the three questions and the corresponding subscales in the original CEBQ were moderate to high (5) . As used before (40) , data on parental concerns were included as potential confounders of the association between eating frequency and subscales of the CEBQ at 7 years.…”
Section: Eating Behavioursmentioning
confidence: 84%
See 3 more Smart Citations